2016
DOI: 10.2217/nnm-2016-0006
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Monocyte/Macrophage Modulation by Liposome-Entrapped Spironolactone Ameliorates Acute Lung Injury in Mice

Abstract: Aim:To examine the therapeutic/preventive potential of liposome-encapsulated spironolactone (SP; Lipo-SP) for acute lung injury (ALI) and fibrosis. Materials & methods: Lipo-SP was prepared by the film-ultrasonic method, and physicochemical and pharmacokinetic characterized for oral administration (10 and 20 mg/kg for SPloaded liposome; 20 mg/kg for free SP) in a mouse model bleomycin-induced ALI. Results: Lipo-SP enhanced bioavailability of SP with significant amelioration in lung pathology. Mechanistically, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…Moreover, neotuberostemonine (NTS), one of the traditional Chinese medicines included in all versions of the Chinese Pharmacopoeia, can effectively attenuate BLM-induced lung fibrosis via suppressing the recruitment and polarization of M2 macrophages [ 122 ]. Intriguingly, Ji et al demonstrated that mineralocorticoid receptor (MR) antagonism by liposome-encapsulated spironolactone (Lipo-SP) could alleviate bleomycin-induced acute pulmonary injury and fibrosis, partially by reducing circulating inflammatory Ly6C high monocyte expansion and repressing alternatively activated mononuclear phagocytes in the alveolar compartment [ 123 , 124 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, neotuberostemonine (NTS), one of the traditional Chinese medicines included in all versions of the Chinese Pharmacopoeia, can effectively attenuate BLM-induced lung fibrosis via suppressing the recruitment and polarization of M2 macrophages [ 122 ]. Intriguingly, Ji et al demonstrated that mineralocorticoid receptor (MR) antagonism by liposome-encapsulated spironolactone (Lipo-SP) could alleviate bleomycin-induced acute pulmonary injury and fibrosis, partially by reducing circulating inflammatory Ly6C high monocyte expansion and repressing alternatively activated mononuclear phagocytes in the alveolar compartment [ 123 , 124 ].…”
Section: Discussionmentioning
confidence: 99%
“…Flow cytometry (FCM) analysis was performed using a Cytomics FC500 cytometer (Beckman-Coulter, Miami, FL) according to previous work [ 59 ]. Fifty microliters of EDTA-anticoagulated whole blood was stained with antibody mix containing 10 μL PerCP-Cy5.5 (clone 1A8), 10 μL FITC-Ly6C (clone HK1.4), and 10 μL PE-CD11b antibodies, incubated for 15 min at room temperature in the dark.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the protection reported to be provided by spironolactone, specific actions against SARS-CoV-2 actions have been proposed, including increased availability of free circulating ACE2 in response to a hyperreninemic state induced by MR antagonism [98][99][100][101][102][103][104], reduction of TMPRSS2 expression due to antagonism of AR [105][106][107], reversal of RAAS abnormalities induced by obesity [108,109], and possible direct antiinflammatory and anti-viral actions that hamper lung injuries [110][111][112][113][114][115][116][117][118][119][120][121]. There are currently three ongoing clinical trials with spironolactone [122][123][124].…”
Section: Of Moderate Relevancementioning
confidence: 99%